Bilateral inguinal hernias: simultaneous or sequential repair?. Issue 751 (May 1988) - Stott, M. A.; Sutton, R.; Royle, G. T.
Abstract : Two hundred and forty four patients underwent either simultaneous bilateral inguinal hernia repair (n = 122) or unilateral inguinal hernia (n = 122) repair at a general hospital between January 1971 and December 1981. The two groups of patients were matched for age and sex. Both groups had a similar overall incidence of post-operative complications and in both groups the duration of post-operative stay and duration of operating time were similar. Chest infections developed in 12 patients after bilateral repair and in 3 patients after unilateral repair (P less than 0.02). All patients were assessed prospectively from 4 to 15 years after operation, when no significant difference in the number of recurrent hernias was found. Our results suggest that simultaneous bilateral inguinal herniorrhaphy is economical in terms of both operating time and duration of hospital stay, and that this economy is not bought at a cost of increased short term morbidity or long-term recurrence rate.